Improved BEC SMOS Arctic Sea Surface Salinity product v3.1 - Martínez, Justino; Gabarró, Carolina; Turiel, Antonio; González-Gambau, Verónica; Umbert, Marta; Hoareau, Nina; González-Haro, Cristina; Olmedo, Estrella; Arias, Manuel; Catany, Rafael; Bertino, Laurent; Raj, Roshin P.; et al. (2021)
Measuring salinity from space is challenging since the sensitivity of the brightness temperature ( TB ) to sea surface salinity (SSS) is low (about 0.5 K / psu ), while the SSS range in the open ocean is narrow (about 5 psu, if river discharge areas are not considered). This translates into a high accuracy requirement of the radiometer (about 2–3 K). Moreover, the sensitivity of the TB to SSS at cold waters is even lower (0.3 K / psu ), making the retrieval of the SSS in the cold waters even more challenging. Due to this limitation, ESA launched a speciﬁc initiative in 2019, the Arctic+Salinity project (AO/1-9158/18/I-BG), to produce an enhanced Arctic SSS product with better quality and resolution than the available products. This paper presents the methodologies used to produce the new enhanced Arctic SMOS SSS product (Martínez et al. , 2020) . The product consists of 9-day averaged maps in an EASE 2.0 grid of 25 km. The product is freely distributed from the Barcelona Expert Center (BEC, http://bec.icm.csic.es/ ) with the DOI number: 10.20350/digitalCSIC/12620 . The major change in this new product is its improvement of the effective spatial resolution that permits better monitoring of the mesoscale structures (larger than 50 Km), which beneﬁts the river discharges monitoring.